Marušičev zbornik Zgodovinopisec zahodnega roba - prof. dr. Branku Marušiču ob 80-letnici - Kolenc, Petra; Zuljan Kumar, Danila; Luthar, Oto; Svoljšak, Petra (ZRC SAZU, Založba ZRC, 2019)
Important anniversaries of prominent historians have become traditional opportunities for the gift to the celebrator in the form of scientific contributions from his colleagues and the colleagues who have worked with him fruitfully or are still doing so. Marušičev zbornik is a tribute to one of the leading historians of the Slovene region in contact with its western neighbors, historian prof. Branko Marušič at the age of 80. He has created a very important oeuvre, while outlining basic research directions, which some have continued to gain. One of the prominent results of this "scientific transfer" is the present scientific monograph, with the highly significant subtitle, Zgodovinopisec zahodnega roba (The Historian of West Edge). In a single volume, it represents the contribution of different generations of historians to new insights into the history of coastal space, especially that of the borderland, which throughout history has encountered coexistence with "the other." Different historical sources and their careful analyzes and interpretations, which the authors place in different time contexts, contribute to new or original scientific knowledge. The monograph is actual and important for the development of historiography, also because of the development of Slovenian scientific terminology.